Evaluation of the Involvement of a Police Officer in Schools of the Killarney District - Ellis, E. N.; Vancouver Board of School Trustees (British Columbia). Dept. of Planning and Evaluation ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
An officer on the Youth Detail of the Vancouver Police Department has been actively participating since April 1972, in activities at the Killarney Secondary School and six of its feeder elementary schools. The purpose of the involvement of the officer was to bring about more positive attitudes toward authority and the police and to contribute to the improvement of relationships between youth and the police. In the present study, comparisons were made between "experimental" and "control" groups in terms of pre-treatment scores (November 1972) post-treatment scores (June 1973) and changes in scores on a thirty-eight item scale of student attitudes toward police officers. An analysis was made of the performance of students on selected critical items and of the reactions of teachers and principals to the project. A summary was made of student suggestions of ways by which better relationships could be established between students and the police. The officer's involvement in the schools has enabled pupils to view the policeman as a trusted friend. At the end of the 1972-73 school year students in these schools had a more positive attitude toward the police than did the control group. Recommendations were made for the continuation and extension of the program and for an evaluation of the long-range effects. See TM003478 for a related document. (Author/MLP)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Attitude Change; Elementary Schools; Police; Police School Relationship; Program Evaluation; Secondary Schools; Student Attitudes; Canada